Providing Out-of-School Adolescent Girls with Skills : Situation Analysis for Malawi - Khan, Ayesha; Mupuwaliywa, Mupuwaliywa (World Bank, Washington, DC, 2016)
Promoting relevant technical and life skills is one option to empower adolescent girls by increasing their capacity to generate income and therefore by enhancing their bargaining power within the household. This Note presents a situation analysis of the current skills set and employment outcomes of adolescents (aged 15-19 years) in Malawi, with a focus on adolescent girls. The Note draws on several sources of data, including the Malawi Labor Force Survey 2013. The data reveal that female adolescents are as active in the labor market as their male counterparts, but are more likely to be unemployed and earn less. Furthermore, girls report marriage, pregnancy, or family responsibilities as constraints when making decisions about investments in education and training, or seeking work. However, further analysis is necessary to understand how these trends affect choices made by adolescent girls and their households.